The unity of the senses - Hanson, Esther Elizabeth (My University, 1903)
Introduction: The parts of the human body that chiefly interests the student of mental science are the nerves and nerve centers, principally collected in the brain, the organs of sense, and the muscular system. The brain is the principal organ of the mind. We know that the brain is the principal organ of the mind from the local feelings that we experience during mental excitement. In most cases of bodily irritation, we can assign the place or seat of the disturbance. In ordinary circumstances we have no local consciousness of mental action, but in time of great mental agitation, or after some usual exertion of thought, the aching or oppression in the head tells where the seat of action is, precisely as aching limbs prove what muscles have been exercised during a long day's march. If the brain is diseased or injured it impairs in some way or another the power of the mind. For example, if a person receives a blow on the head it will destroy consciousness for a time. The nervous system may be divided into two parts. First, the central nervous system, consisting of the brain and the spinal cord. Second, the peripheral nervous system. We may include under the peripheral nervous system the nerve fibers running from the central system to the various parts of the body, and all collections of nerve cells outside of the great central nervous organs. In the part last mentioned are included the nervous mechanisms of the ear, eye, tongue, nose, skin, viscera and the nerves connecting them with the brain or spinal cord. The units of the nervous system are the nerve fibers, and nerve cells. We find that the entire nervous system is formed on a uniform plan. Cells or aggregations of cells, are joined to each other by nerve fibers; and all are connected directly with the brain.
Citation: Hanson, Esther Elizabeth. The unity of the senses. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Nervous System; Senses; Human Anatomy; Theses